2021
DOI: 10.3168/jds.2020-19729
|View full text |Cite|
|
Sign up to set email alerts
|

Blood parameters of young calves at abattoirs are related to distance transported and farm of origin

Abstract: Nonreplacement dairy calves, or bobby calves, are fasted and transported to abattoirs from as young as 5 d of age in Australia. The aims of this cross-sectional observational study were (1) to assess the welfare status, as measured by blood parameters, of bobby calves in the commercial supply chain after transport and lairage, and (2) to assess whether distance and duration of transport are risk factors for poor bobby calf welfare, as measured by blood parameters. We hypothesized that bobby calves transported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
(43 reference statements)
4
19
3
Order By: Relevance
“…Decreased GLUC is a well-known feature of calves that experience fasting or the feeding of diets that do not meet energy demands (Kinsbergen et al, 1994b;Marcato et al, 2020;Roadknight et al, 2021). Severity and duration of illness and a concomitant alteration of milk intake provide an obvious explanation for the association between hypoglycemia and NO in calves of the present study.…”
Section: Jdsmentioning
confidence: 61%
“…Decreased GLUC is a well-known feature of calves that experience fasting or the feeding of diets that do not meet energy demands (Kinsbergen et al, 1994b;Marcato et al, 2020;Roadknight et al, 2021). Severity and duration of illness and a concomitant alteration of milk intake provide an obvious explanation for the association between hypoglycemia and NO in calves of the present study.…”
Section: Jdsmentioning
confidence: 61%
“…The transport to the abattoir is a dangerous situation for the health of the animals, in particular when the driving condition, driving style and suspension are not optimal and can cause vibration and loss of balance in the animals [ 11 , 12 ]. Some studies reported that the length of the journey can influence blood parameters and the mortality of animals [ 13 , 14 ]. Both respiratory diseases and tail injuries are associated with the reduction of performance in pigs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRT ≥ 3 s reflects a 4.3% reduction in hydration in dairy calves compared with lower refill times ( 91 ). PCV is also typically elevated in dehydration ( 92 ), as shown in calves from V/W embryos compared with calves from F/T embryos but not within calves from not cryopreserved embryos. Rectal temperature and respiration rates decrease by dehydration ( 91 ), but such parameters did not change between calf types.…”
Section: Discussionmentioning
confidence: 99%